El abuso sexual a niñas, niños y adolescentes: un secreto familiar, un problema familiar, un problema social - Palacios, José Rodolfo (Revista Electrónica Educare, 2008)
This investigation has the purpose of identifying how to prevent through educational processes, and then eradicate, the sexual abuse against children and adolescents in rural communities from Salvador, Guatemala, Honduras and Nicaragua.The premise is that sexual abuse cannot be approached in an isolated way; it requires integral and committed actions of the institutions in charge of children and adolescents’ integral protection and development.This implies considering: the legal framework, the response offered by government and private organizations towards the prevention and attention of rights as well as their actions to penalize and restore the violated rights; the role of families as main responsible of the well being of their children and the role of children and adolescents.